Effect of temperature on the stability and optical properties of SiO2-water nanofluids for hybrid photovoltaic/thermal applications. (5th July 2020) - Adam, Saadelnour Abdueljabbar; Ju, Xing; Zhang, Zheyang; Lin, Jianqing; Abd El-Samie, Mostafa M.; Xu, Chao
Highlights: We investigated the stability and optical properties of SiO2 -H2 O nanofluids (NFs) at elevated temperatures. Reducing the sonicating temperature during the fabrication process helped to improve the NF stability. Adding of nanoparticles helped to increase the spectrum absorption ability of NF. The NF absorptance decreased with the increase of working temperature. Abstract: Nanofluids (NFs) have been investigated as optical filters for photovoltaic/thermal applications, since they are more effective to produce heat with higher temperatures. However, the effect of temperature on both the stability and optical property of NFs has been little reported. In this work, we synthesized the SiO2 -H2 O NFs under different conditions and different nanoparticle volume fractions, and investigated the NF dispersion stability and optical properties at elevated temperatures. We analyzed the effects of several factors including the sonication temperature, the exposure temperature, the nanoparticle volume fraction and the exposure time. The results showed that reducing the maximum sonicating temperature during the NF fabrication process is beneficial to prolonging the NF stability, and the prepared NF stability was rather good with the maximum sonicating temperature of 30 °C. The absorptance of NFs decreased when the exposure temperature increased from 25 to 90 °C, and agglomeration more likely occurred for higher exposure temperatures. It is also found that the adding of nanoparticles helped to increase the spectrum absorption ability of NF. As a result, the overall energy efficiencies of the photovoltaic/thermal device using the NFs as the optical filter can be increased compared with that using the water filter.